2018
DOI: 10.3390/min8010015
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Stage Flotation for the Removal of Ash from Fine Graphite Using Mechanical and Centrifugal Forces

Abstract: Graphite ore collected from Hunan province, south China was characterized by chemical analysis, X-ray diffraction, and optical microscopy. Rougher and multi-stage flotation tests using a mechanical flotation cell and a flotation column containing an additional centrifugal force field were carried out to promote its grade and economic value. In rougher flotation, both the mechanical flotation cell and flotation column reduced the ash content of the graphite ore from 15.43% to 10.8%, while the yield of the flota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The release analysis test was performed to determine the floatability of the coking coal fines according to Chinese Standard GB/T 36167-2018 (Methods for coal preparation laboratory timed-release flotation analysis). Flotation release tests were performed based on published literature [40][41][42]. The flotation time was constant at 3 min for different flotation stages of release flotation.…”
Section: Batch Flotation Testmentioning
confidence: 99%
“…The release analysis test was performed to determine the floatability of the coking coal fines according to Chinese Standard GB/T 36167-2018 (Methods for coal preparation laboratory timed-release flotation analysis). Flotation release tests were performed based on published literature [40][41][42]. The flotation time was constant at 3 min for different flotation stages of release flotation.…”
Section: Batch Flotation Testmentioning
confidence: 99%
“…Many studies have claimed that the flotation column technique yields higher recovery with better grades for fine particles during the cleaner stage. 10 13 Meanwhile, several works performed by the authors 14 , 15 have shown that mechanical flotation cells have advantages in recovering coarse particles at rougher or scavenger stages. In recent years, combined column and cell flotation processes have been applied to many mineral beneficiation processes and have improved the overall performance.…”
Section: Introductionmentioning
confidence: 99%
“…In downhole hydrocyclone, as a key component of the downhole in situ separation system, the performance and flow field characteristics play a decisive role. Hydrocyclones are widely used in various engineering processes because of their simple design, flexible operation, large capacity, and low maintenance costs [12,13]. Flow field characteristics are highly complex multiphase structures in a hydrocyclone.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of a hydrocyclone to recycle NGH and desand during NGH exploitation is a novel idea, and its performance needs to balance the recovery rate of the NGH outlet and the removal rate of the sand outlet. Nevertheless, the flow field and Hydrocyclones are widely used in various engineering processes because of their simple design, flexible operation, large capacity, and low maintenance costs [12,13]. Flow field characteristics are highly complex multiphase structures in a hydrocyclone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation